Histopathological Correlation of Atypical (C3) and Suspicious (C4) Categories in Fine Needle Aspiration Cytology of the Breast. (23rd September 2013) - Goyal, Prashant; Sehgal, Shelly; Ghosh, Soumyesh; Aggarwal, Deepti; Shukla, Pritesh; Kumar, Awanindra; Gupta, Ruchika; Singh, Sompal
Abstract : Introduction. According to the National Cancer Institute (NCI) guidelines in 1996, breast lesions are categorized as C1 to C5 on fine needle aspiration (FNA) cytology. Very few studies are available in the English literature analyzing histopathology outcome of C3 (atypical, probably benign) and C4 (suspicious, probably malignant) lesions. Our study aims to correlate FNA cytology of breast lump diagnosed as C3 and C4 lesion with histopathological examination. Methods. During a period of 2 years, 59 cases of C3 and 26 cases of C4 were retrieved from total 1093 cases of breast FNA. All the cases were reviewed by two cytopathologists independently. The final 24 cases of C3 and 16 cases of C4 categories were correlated with histopathological diagnosis. Result. Among C3 category, 37.5% revealed malignant findings, whereas of C4 category, 87.5% were malignant on histopathology. This difference was statistically significant (P = 0.0017 ). Sensitivity, specificity, positive predictive values, and negative predictive value of C4 category in diagnosing breast malignancy were 60.8%, 88.2%, 87.5%, and 62.5%, respectively. Conclusion. Although FNAC is simple, safe, cost-effective and accurate method for diagnosis of breast masses, one must be aware of its limitations particularly in C3 and C4 categories. Also, since both these categories carry different probabilities of malignancy and thus different management, we therefore, support maintaining C3 and C4 categories.